Integrative taxonomy reveals the exceptional species diversity of Eudonia (Lepidoptera: Crambidae) in Tibet, China. Issue 1 (2nd January 2019) - Li, Weichun
Abstract : The genus Eudonia is rarely recorded in Tibet despite having a wide occurrence in the plateau. In the taxonomy of the genus, the morphological characters are insufficient to delimit the closely related congeners due to the subtly interspecific differences and conspicuously intraspecific variability. In this study, the Tibetan species are studied with an integrative approach using molecular data and morphological characters. It is found that the number of Eudonia species in Tibet accounts for about 20% of the total species previously catalogued for the genus in China. Five species are described as new to science: Eudonia galonglaensis Li, sp. nov., E. varians Li, sp. nov., E. triangulata Li, sp. nov., E. angusta Li, sp. nov., and E. bomiensis Li, sp. nov. The potential distribution of Chinese Eudonia is predicted and illustrated using MaxEnt and DIVA-GIS. The results reveal the exceptionally high species diversity of Eudonia in Tibet for the first time, demonstrate that the integrative morphological and molecular approach is highly effective for resolving the difficult-to-distinguish morphologies, and predict the region of China to the south of 35°N and to the east of 95°E as having potentially high Eudonia species diversity. http://www.zoobank.org/urn:lsid:zoobank.org:pub:EA3C5D21-9674-46E4-838D-48D5A098314B